HUBUNGAN ANTARA AKTIVITAS ANAK PADA PENERAPAN METODE PROYEK DENGAN SIKAP KERJA SAMA ANAK USIA DINI(Penelitian di RA Al Mizan Babakan Kabupaten Garut) - Gina Siti Ulfah; Heri Hidayat (CV. ADIBA AISHA AMIRA, 2025)
Based on a preliminary study conducted by researchers at RA Al Mizan Babakan, Garut Regency, researchers saw that conditions were not in harmony and there were still children who did not have the same work attitude. Use of the project method. The subjects of this research were 14 students from RA Al Mizan Babakan, Garut Regency. The results of the calculation of Variable Meanwhile, for variable Y, Early Childhood Cooperation Attitudes, an average value of 70 was obtained. This figure is in the interval 70-79 in the good category. In this study, there was a relationship value of 0.64, this figure was in the interval 0.600 – 0.799 in the strong category. This is also shown by the results of hypothesis testing which obtained ????ℎ???????????????????? namely 2.91 and ???????????????????????? with db = 7 at the 5% significance level of 1.78229. Therefore, it can be concluded Thar ????ℎ???????????????????? > ???????????????????????? then it can be interpreted that ????0 is rejected and ???????? is accepted. significance of the cooperative attitude of early childhood in RA Al Mizan, Garut Regency. The results of the significance test showed that children's activities in applying the project method to the cooperative attitude of early childhood contributed 40.96% to the cooperative attitude of early childhood. This means that there are 59.04 more cooperative attitudes of early childhood children at RA Al Mizan Garut.